2004
DOI: 10.1093/bja/aeh054
|View full text |Cite
|
Sign up to set email alerts
|

Unconscious learning during surgery with propofol anaesthesia † †This article is accompanied by Editorial II

Abstract: Learning during anaesthesia seems more likely to occur during rather than before surgical stimulation at comparable anaesthetic depth. We hypothesize that surgical stimulation facilitates learning during anaesthesia, independently of its effects on anaesthetic depth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
44
0
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 25 publications
8
44
0
5
Order By: Relevance
“…Interestingly, this neuronal associative encoding takes place while animals are conditioned under chloral hydrate anesthesia, demonstrating that neuronal associative learning can occur in a non-conscious state. Such non-conscious learning has also been demonstrated in memory-encoding studies with human subjects [22,23]. Similarly, we have recently shown that a subpopulation of neurons in the mPFC that receive an orthodromic input from the BLA actively encode and express emotional associative learning in the same Pavlovian paradigm, demonstrating that neuronal subpopulations within both the mPFC and amygdala are capable of actively encoding and expressing emotional associative learning.…”
Section: Introductionsupporting
confidence: 73%
“…Interestingly, this neuronal associative encoding takes place while animals are conditioned under chloral hydrate anesthesia, demonstrating that neuronal associative learning can occur in a non-conscious state. Such non-conscious learning has also been demonstrated in memory-encoding studies with human subjects [22,23]. Similarly, we have recently shown that a subpopulation of neurons in the mPFC that receive an orthodromic input from the BLA actively encode and express emotional associative learning in the same Pavlovian paradigm, demonstrating that neuronal subpopulations within both the mPFC and amygdala are capable of actively encoding and expressing emotional associative learning.…”
Section: Introductionsupporting
confidence: 73%
“…Also note that stimuli in this study were presented before surgery, whereas typical studies present them during surgery. We have hypothesized that the surgical stress response facilitates implicit priming during anesthesia (Deeprose et al, 2004;Stapleton & Andrade, 2000). If we are correct, then this study is not a strong test of the hypothesis that priming can occur when surgical patients are unconscious.…”
Section: Auditory Evoked Potentialsmentioning
confidence: 85%
“…Studies by Mü nte and colleagues suggest continued auditory processing during deep anesthesia, shown by the presence of mismatch negativity in the EEG response to ÔoddballÕ auditory stimuli Quandt et al, 2004). If at least a small amount of auditory processing persists when people are anesthetized, then memory formation for this information may be facilitated by the high levels of catecholamines released in response to surgery and known to act via the amygdala to facilitate memory formation for emotional stimuli (Deeprose, Andrade, Varma, & Edwards, 2004;Stapleton & Andrade, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Fell (email: juergen.fell@ukb.uni-bonn.de, Tel. : +49-228-2879347, Fax: +49-228-2876294) ing deep sedation found evidence for nondeclarative (implicit), but no evidence for declarative (explicit) memory, i.e., for subsequent conscious recollection of events and facts (e.g., Bethune et al 1992;Cork et al 1996;Deeprose et al 2004;Munte 1999). However, in studies implementing the so-called process dissociation procedure (Jacoby 1991), evidence for some kind of declarative memory formation during deep anesthesia was reported (Kerssens et al 2002;Stapleton et al 2000).…”
Section: Introductionmentioning
confidence: 99%